Price Risk and Risk Management in Agriculture - Udo Broll; Peter Welzel; Kit Pong Wong (Contemporary Economics, 2013)
This note studies the risk-management decisions of a risk-averse farmer. The farmer faces multiple sources of price uncertainty. He sells commodities to two markets at two prices, but only one of these markets has a futures market. We show that the farmer's optimal commodity futures market position, i.e., a cross-hedge strategy, is actually an over-hedge, a full-hedge, or an under-hedge strategy, depending on whether the two prices are strongly positively correlated, uncorrelated, or negatively correlated, respectively.
Keywords: D73; D78; D83; 330; agricultural price risk; risk management; commodity futures; correlation; cross-hedge